Mixed-Metal Ni2+–Mn2+ Paddle Wheels in the Metal–Organic Framework DUT-8(Ni1–xMnx) as Electron Paramagnetic Resonance Probes for Monitoring the Structural Phase Transition - Mendt, Matthias; Maliuta, Mariia; Ehrling, Sebastian; Schwotzer, Friedrich; Senkovska, Irena; Kaskel, Stefan; Pöppl, Andreas (Journal of Physical Chemistry C, 2022)
The metal–organic framework (MOF) DUT-8(Ni) [Ni2(2,6-ndc)2(dabco), 2,6-ndc = 2,6-naphthalenedicarboxylate, dabco = 1,4-diazabicyclo[2,2,2]octane] is an important representative of flexible pillared layer MOFs, providing improved performance as an adsorbent in gas delivery and separation applications. To enable electron paramagnetic resonance (EPR) investigations, DUT-8(Ni) was doped with Mn2+, and two variants of the compound were investigated, which differ in crystal size and flexibility. For the rigid variant, an intense EPR signal was observed, which could be assigned to the electron spin S = 3/2 state of Ni2+–Mn2+ paddle wheel (PW) units. The EPR characteristics of this magnetic Ni2+–Mn2+ PW probe open up a considerably larger temperature range for EPR-detected adsorption investigations, compared to the previously studied Cu2+ and Co2+ doping as paramagnetic probes. As a proof of concept, we measured the EPR signal of Ni2+–Mn2+ PWs of the flexible variant in situ during CO2 adsorption and desorption at 195 K to monitor the framework responsiveness of this material. In comparison to its rigid variant, the Ni2+–Mn2+ EPR signal was less intense here since a smaller amount of Mn2+ ions is incorporated into the large crystals of the flexible DUT-8 phase. However, the EPR sensitivity of the Ni2+–Mn2+ PWs was still sufficient to probe in situ the CO2 adsorption-triggered phase transition of the flexible DUT-8 material.
CRIS-Team Scopus Importer:2022-04-14